The second-order self-associated orthogonal sequences - P. Maroni; M. Ihsen Tounsi (Journal of Applied Mathematics)
The aim of this work is to describe the orthogonal polynomials sequences which are identical to their second associated sequence. The resulting polynomials are semiclassical of class s≤3. The characteristic elements of the structure relation and of the second-order differential equation are given explicitly. Integral representations of the corresponding forms are also given. A striking particular case is the case of the so-called electrospheric polynomials.